ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI GENERASI MILENIAL BERWIRAUSAHA (STUDI PADA GENERASI MILENIAL DI KECAMATAN KOTA WAINGAPU) - Lewa, Melki Hamba; Situmorang, Tumpal P (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research is motivated by the increasing unemployment rate currently. However, as many as 247 new business units grew because they were driven by the millennial generation in Waingapu City District. This research aims to determine the influence of entrepreneurial knowledge, use of technology and income expectations on entrepreneurial decisions of the millennial generation in Waingapu City District. The population in this study was the entire millennial generation who are entrepreneurs in Waingapu City District and a sample of 80 respondents. The data collection technique uses a questionnaire method. The data analysis method uses descriptive statistical analysis, validity test, reliability test, multiple linear regression, classical assumption test, coefficient of determination test and hypothesis testing. The research results show that 1) entrepreneurial decisions have a positive and significant effect on entrepreneurial decisions, 2) the use of technology has no effect on entrepreneurial decisions, 3) income expectations have a positive and significant effect on entrepreneurial decisions. It can be concluded that entrepreneurial decisions and income expectations have an influence, while the use of technology has no influence on the entrepreneurial decisions of the millennial generation in Waingapu City District.